Safety and efficacy of eculizumab in the prevention of antibody‐mediated rejection in living‐donor kidney transplant recipients requiring desensitization therapy: A randomized trial. Issue 10 (19th April 2019) - Marks, William H.; Mamode, Nizam; Montgomery, Robert A.; Stegall, Mark D.; Ratner, Lloyd E.; Cornell, Lynn D.; Rowshani, Ajda T.; Colvin, Robert B.; Dain, Bradley; Boice, Judith A.; Glotz, Denis; ,
Abstract : We report results of a phase 2, randomized, multicenter, open‐label, two‐arm study evaluating the safety and efficacy of eculizumab in preventing acute antibody‐mediated rejection (AMR) in sensitized recipients of living‐donor kidney transplants requiring pretransplant desensitization (NCT01399593). In total, 102 patients underwent desensitization. Posttransplant, 51 patients received standard of care (SOC) and 51 received eculizumab. The primary end point was week 9 posttransplant treatment failure rate, a composite of: biopsy‐proven acute AMR (Banff 2007 grade II or III; assessed by blinded central pathology); graft loss; death; or loss to follow‐up. Eculizumab was well tolerated with no new safety concerns. No significant difference in treatment failure rate was observed between eculizumab (9.8%) and SOC (13.7%; P  =   .760). To determine whether data assessment assumptions affected study outcome, biopsies were reanalyzed by central pathologists using clinical information. The resulting treatment failure rates were 11.8% and 21.6% for the eculizumab and SOC groups, respectively (nominal P  =   .288). When reassessment included grade I AMR, the treatment failure rates were 11.8% (eculizumab) and 29.4% (SOC; nominal P  =   .048). This finding suggests a potential benefit for eculizumab compared with SOC in preventing acute AMR in recipients sensitized to their living‐donor kidney transplants (EudraCT 2010‐019630‐28). Abstract : In this study of terminal complement inhibition to prevent acute antibody‐mediated rejection in living‐donor kidney transplant recipients with preformed donor‐specific antibodies, prophylactic eculizumab does not significantly reduce the treatment failure rate compared with standard of care, but biopsy reanalysis suggests a benefit for eculizumab in preventing AMR in these patients. See the article by Glotz et al on page2865 .